Two new species of the vampire catfish genus Paracanthopoma (Siluriformes: Trichomycteridae: Vandelliinae) from Brazil and Venezuela with comments on generic diagnostic characters - Henschel, Elisabeth; Baskin, Jonathan N.; Lujan, Nathan K. (Zootaxa, 2026)
The blood-feeding candiru genus Paracanthopoma was monotypic for over 85 years, with ten new species being described in the last four years. Despite this rapid growth, interspecific relationships and boundaries between it and the closely related genus Paravandellia remain intensively debated, with clarification of these boundaries being hampered by the lack of a formal phylogenetic analysis focused on the Vandelliinae. Here, we describe two new species of Paracanthopoma from Brazil and Venezuela based on photomicroscopy, cleared and stained specimens, and µCT imagery and reexamine the current taxonomic status of the genus. Paracanthopoma ventuarensis sp. nov. is described from the Orinoco River basin and Parac. jiparanaensis sp. nov. from the Machado River in northern Brazil, where Parac. parva and Parac. malevola also occur. The two new species here described share with Parac. daemon, Parac. parva, Parac. carrapata, and Parac. truculenta a spine-like anterior process on the parietosupraoccipital and an azygous s6 supratemporal lateral-line pore, thus being allocated to this putative clade.